Alkene Carboboration Enabled by Synergistic Catalysis. Issue 38 (11th August 2014) - Smith, Kevin B.; Logan, Kaitlyn M.; You, Wei; Brown, M. Kevin
Abstract A synergistic Pd/Cu system for the coupling of alkenes, (Bpin)2 (pin=pinacolate), and aryl/vinyl bromides is disclosed. This method allows for the catalytic generation of secondary Csp3Cu nucleophiles in situ and subsequent Pd‐catalyzed cross‐coupling.